Factors Affecting Psychological Dynamics of Esports Athletes - Nadia Aulia Nadhirah; Azriel Arriadi Hidayat; Dodi Suryana; Ipah Saripah; Ahmad Rofi Suryahadikusumah (Journal of Education and Counseling (JECO), 2022)
Dozens of years ago, it was difficult to even consider playing video games as a career path. Following immense development in the last decade, esports has evolved into a luxurious, enjoyable, and profitable industry. It has now become an interesting, appealing industry for young people. However, despite the media’s glorification towards the industry, there is so much pressure, obligation, and factors that would turn a seemingly fun and simple occupation into a stressful line of work, contrary to how medias and the public perceives this industry. This article will dive deeply into what is going on behind the scenes, using the study case method, in which the author is directly involved in the esports industry of the Dota 2 game. Following the observations, it can be concluded that esports athletes are heavily affected by external demands, media scrutiny, their daily routine, habits, nutrition, and internal conflicts within the team’s environment.